Correlation between Central Venous Pressure and Femoral Vein Diameter - Syed, Fatima Tassadaq; Burki, Ahmed Mujadid Khan; Kashif, Sanum (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the correlation between central venous pressure and femoral vein diameter. Study Design: Cross sectional analytical study. Place and Duration of Study: Surgical Intensive Care Unit, Combined Military Hospital (CMH), Rawalpindi Pakistan, from May to Sep, 2025. Methodology: This study included 84 patients. Patients who were 18 years or older, on mechanical ventilation with central venous catheter passed in internal jugular or subclavian veins were included in study. Those with deep venous thrombosis, raised intraabdominal pressure were excluded. Central venous pressure (CVP) was measured with manual manometer technique and was recorded in ‘centimetres of water’ (cm H2O). Femoral vein diameter (FVD) was measured non-invasively with linear transducer below sapheno femoral junction and was recorded in ‘centimetres’ (cm). Both measurements were taken with patient in supine position and were recorded by two critical care medicine residents who were blinded to each other results. Results: There was a moderate correlation between femoral vein diameter and central venous pressure (r=0.40, p<0.001). Regression result suggested that a 1cm increase in FVD was associated with a 5.32 cm increase in CVP and was significant at the 99%CI. Conclusion: Considering a moderate correlation between central venous pressure and femoral vein diameter, FVD may be used as a marker for intravascular volume status however, further studies are needed.